Electric transportation and electroreception in hummingbird flower mites - Carlos García-Robledo; Diego Dierick; Konstantine Manser (Proceedings of the National Academy of Sciences, 2025)
Electric fields in terrestrial environments are used by caterpillars to detect their predators, as foraging cues by pollinators, and facilitate ballooning by spiders. This study shows that electric fields facilitate transportation and detection of hummingbirds in a guild of tropical phoretic mites. Hummingbird flower mites feed on nectar and pollen and complete their life cycle inside flowers. Mites colonize new flowers by hitching rides on hummingbird beaks. Flower mites emerge from hummingbird nostrils and disembark when the beak touches a flower. We tested whether flower mites are attracted to unmodulated electrostatic, or to modulated electric fields with amplitudes and frequencies in the range of those previously reported for hummingbirds. In a laboratory setup, mites were only attracted to modulated electric fields. In a choice experiment between positive or negative polarities, mites almost instantaneously chose positive charges, but only when the field was modulated. Mites display questing behavior, moving their front legs toward an electrostatic source. In experiments where we removed one or both front leg tarsi, we show that modulated fields are detected by sensory structures present in the front legs. We also show that flower mites use electrostatic attraction to bridge the gap to the beaks of hummingbirds, for a few milliseconds becoming one of the fastest terrestrial organisms. Our results confirm that hummingbird flower mites evolved an additional sensory modality — electroreception — to quickly detect hummingbirds and use electrostatics to facilitate transportation onto their hosts.